PENGARUH KUALITAS PELAYANAN APOTEK TERHADAP KEPUASAN PASIEN DI PUSKESMAS MAYAMUK KABUPATEN SORONG - Vivid Wantari; Irwandi Irwandi (JURNAL ETNOFARMASI, 2025)
Service quality is an important factor that can shape patient satisfaction with the health center so that their loyalty as consumers of health services is created. Based on initial observations made by researchers, service problems found at the Mayamuk Community Health Center pharmacy in Sorong Regency were found during the drug service process, namely patients had to wait a long time because of the long preparation time for drugs caused by the large number of prescriptions, and long queues often cause discomfort for patients, it will be a serious problem for the health center because it can affect the satisfaction of outpatients in obtaining health services. This study aims to determine how influential the quality of pharmacy services is on patient satisfaction at the Mayamuk Community Health Center with a sample of 95 people with the calculation of the Slovin formula. The method used is quantitative research. The results of the study showed that the variable of pharmacy service quality (X1) has a significant influence on patient satisfaction (X2) with a significance value of 0.00 which is smaller than 0.05.